Efecto de cinco dosis de brassinolina natural en naranjilla hibrida (Solanum quitoense) sobre la calidad y tamaño del fruto en el cantón Mejía, provincia de Pichincha Año 2012 - Lahuatte Rojas, Mario Clever (2013)
This research was conducted at the farm located Maria Aurora province of Pichincha, Canton Mejía, Pampas Argentinas industry, raised the following objectives: To evaluate the effect of five doses of natural brassinolina naranjilla hybrid (Solanum quitoense) on the quality and size of the fruit. We applied the design completely randomized block (RCBD) with six treatments and four replications. To determine the difference between means was applied multiple range test of Tukey at 95% probability, the variables evaluated were: number of flowers per inflorescence, number of flowers pollinated, fertilized fruit percentage, days to harvest, weight the fruit (g), fruit diameter (cm), and brix flesh coloration. Using brassinolina showed better physiological and productive responses regarding the use of agrochemicals for fruit set and fruit development in growing naranjilla, the best dose 0135-0145 ml / L of water recorded positive effect on the percentage of fruit variables cuajados 97.62%, 5.53 cm diameter and fruit weight 111.43 g. Brassinolina treatment with intermediate doses of 0.135 ml / l of water allows to achieve greater size and weight. The effect of maturity status provided treatment at doses of 0.165 ml / l of water brassiolina with yellow coloration 35.29 64.71 green with a light green flesh coloration bright. The (º Brix) in the corresponding treatments to the highest dose of brassinolina 0.125 ml / l of water with respect to the control Dacocida (2,4 - D) had the lowest average.